Protective inflammasome activation in AMD - Campbell, Matthew (Henry Stewart Talks, 2016)
Prevalence & forms of AMD, The NLRP3 inflammasome in AMD, Laser-induced CNV, IL-18 anti-angiogenic properties, IL-18 regulation of vascular permeability in choroid, IL-18 in human & primate retinal pigment epithelium (RPE), IL-18 regulation of VEGF activity, secretion & expression levels, IL-18 regulation of CNV development, IL-18 utility as an additive therapy for wet AMD